NATIONAL INNOVATION SYSTEM OF UZBEKISTAN – A NEW OPPORTUNITY FOR ECONOMIC DEVELOPMENT - Mirzaev Kulmamat Djanzakovich (Western European Studies, 2024)
The article examines the national innovation system of Uzbekistan as a key tool for stimulating the economic development of the country in modern conditions. The main aspects of scientific and technological progress and innovative activity in the country are analyzed, its main advantages and challenges are identified. The article also discusses the strategies and measures taken by the government of Uzbekistan to develop the national innovation system and its impact on the economic development of the country as a whole.
Keywords: innovation system; economic development; scientific and technological progress